Landscape and identity in the adaptable city - Szabó, Árpád; Szabó, Gyöngyvér; Balogh , Péter István (4D Journal of Landscape Architecture and Garden Art, 2013)
The Europan platform for architecture, landscape and urban design has been looking for design solutions in the frame of the competition for almost 25 years. The general theme of the competition is the European urbanity, to make contribution to a higher quality of urban life affected by urban sprawl and various other transformations. The lasting capability for its renewal lies in a very simple notion: at a given time the city and its public spaces have to tackle the same problems as the world has to. Working with the current social and economic changes, the Europan aims to redefine the actual problems of the European city in every two years and evolve strategies that might show a way to develop. While in the early 2000s, by reacting on the technological boom Europan has been searching the ways of how a city could be smart and simple to use, from the 2010s the emphasis was put on how the separation of private and public realm in the urban environment works.
Keywords: design solutions; Identity; creek